2015
DOI: 10.18016/ksujns.10904
|View full text |Cite
|
Sign up to set email alerts
|

Niğde İli Koyunculuk İşletmelerinin Yapısal Özellikleri ve Sorunları Üzerine Bir Araştırma

Abstract: Geliş A Research on Structural Characteristics and Problems of Sheep Breeding in NigdeABSTRACT: This study was carried out to reveal the present status of sheep farms in Nigde, to detect basic priority problems and to offer some solutions to these problems. In this study, total of 96 sheep farming enterprises were chosen by stratified sampling method to represent the entire province as an example. A survey was conducted to obtain information regarding mating, lambing, milking, shearing, marketing milk and meat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…This will only be possible with education. Gül et al (2022) in Aksaray province and Ceyhan et al (2015) in Niğde province reported in their study that sheep breeders were generally primary school graduates. The study is similar to other studies in this aspect.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…This will only be possible with education. Gül et al (2022) in Aksaray province and Ceyhan et al (2015) in Niğde province reported in their study that sheep breeders were generally primary school graduates. The study is similar to other studies in this aspect.…”
Section: Resultsmentioning
confidence: 95%
“…Gül et al (2022) reported in Aksaray province that female yearling was used breeding at the age of 12 or 20 months. Ceyhan et al (2015) stated that it was as 18.2 months for male yearlings. It is of great importance for male and female animals to be used for breeding to complete their biological and physiological development in terms of herd continuity and reproductive health.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the study, it was reported that 88% of those working in the agricultural sector were concerned about harvesting and sales and that these concerns were mostly (35.6%) due to price instability (Uğur & Buruklar, 2022). In our country, factors such as the low level of education and income of ovine breeders in general and breeding by very small family enterprises with production techniques that continue from father to son cause problems in the input supply of enterprises and the marketing of products (Sarıca et al, 2004;Ceyhan et al, 2015aCeyhan et al, , 2015bKandemir et al, 2015). The education, age, and gender findings obtained in the study were found to be similar to those reported in the literature (Ateş & Çam, 2022;Uğur & Buruklar, 2022).…”
Section: Socio-economic Status Of Breedersmentioning
confidence: 90%
“…The most important problem in sheep breeding enterprises is labor and feed expenses. In addition to these problems, the fact that the owners do not have sufficient knowledge about lamb growth and fattening and that they generally provide breeding from within the enterprise is among the general breeding problems (Ceyhan et al, 2015a(Ceyhan et al, , 2015b.…”
Section: Breeding Practicesmentioning
confidence: 99%